PENERAPAN MODEL JIGSAW BERBANTUAN MEDIA VIDEO ANIMASI DILENGKAPI LKPD TEKA TEKI SILANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII - Umbu Dagha, Asmina; Makaborang, Yohana; Ndjoeroemana, Yohana (Jurnal Biogenerasi, 2025)
This study aims to provide an overview or knowledge about how the Jigsaw model assisted by animated video media equipped with LKPD Crossword puzzles, and to describe the improvement in student learning outcomes after applying the model and learning media. This study is a Classroom Action Research (CAR) using a descriptive quantitative approach. The subjects in this study were students of class VIII A of SMP Negeri 3 Tanah Righu. The data collection instruments used consisted of observation sheets and written tests. The results of the study showed a significant increase in cognitive learning outcomes, from 25% in the pre-cycle to 71% in cycle I, and then increased again to 89% in cycle II. Meanwhile, affective learning outcomes also increased, 36% in cycle I, and reached 82% in cycle II. Therefore, it can be concluded that the application of the Jigsaw learning model assisted by animated video media equipped with LKPD Crossword puzzles can improve the learning outcomes of class VIII A students at Smp Negeri 3 Tanah Righu.